Bioinformatic Analysis of the Type VI Secretion System and Its Potential Toxins in the Acinetobacter Genus - Repizo, Guillermo D.; Espariz, Martín; Seravalle, Joana L.; Salcedo, Suzana P. (Frontiers in Microbiology, 2019)
Several Acinetobacter strains are important nosocomial pathogens, with Acinetobacter baumannii as the species of greatest concern worldwide due to its multi-drug resistance and recent appearance of hyper-virulent strains in the clinical setting. Acinetobacter colonization of the environment and the host is associated with a multitude of factors which remain poorly characterized. Among them, the secretion systems (SS) encoded by Acinetobacter species confer adaptive advantages depending on the niche occupied. Different SS have been characterized in this group of microorganisms, including T6SS used by several Acinetobacter species to outcompete other bacteria and in some A. baumannii strains for Galleria mellonella colonization. Therefore, to better understand the distribution of the T6SS in this genus we carried out an in-depth comparative genomic analysis of the T6SS in 191 sequenced strains. To this end, we analyzed the gene content, sequence similarity, synteny and operon structure of each T6SS loci. The presence of a single conserved T6SS-main cluster (T6SS-1), with two different genetic organizations, was detected in the genomes of several ecologically diverse species. Furthermore, a second main cluster (T6SS-2) was detected in a subgroup of 3 species of environmental origin. Detailed analysis also showed an impressive genetic versatility in T6SS-associated islands, carrying VgrG, PAAR and putative toxin-encoding genes. This in silico study represents the first detailed intra-species comparative analysis of T6SS-associated genes in the Acinetobacter genus, that should contribute to the future experimental characterization of T6SS proteins and effectors.